2018
DOI: 10.1007/s00401-018-1880-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-132 provides neuroprotection for tauopathies via multiple signaling pathways

Abstract: MicroRNAs (miRNA) regulate fundamental biological processes, including neuronal plasticity, stress response, and survival. Here, we describe a neuroprotective function of miR-132, the miRNA most significantly downregulated in neurons in Alzheimer’s disease. We demonstrate that miR-132 protects primary mouse and human wild-type neurons and more vulnerable Tau-mutant neurons against amyloid β-peptide (Aβ) and glutamate excitotoxicity. It lowers the levels of total, phosphorylated, acetylated, and cleaved forms o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 71 publications
(120 reference statements)
4
102
0
1
Order By: Relevance
“…MiRNA‐219 is reduced in AD brain and regulates tau in vivo . MiRNA‐132 is able to protect against tauopathies . We demonstrated that in hippocampus, miRNA‐219 and miRNA‐15a were reduced post dAGEs intervention, while quercetin is able to elevate miRNA‐219 and miRNA‐15a, in addition, quercetin also elevated miRNA‐132.…”
Section: Discussionmentioning
confidence: 73%
“…MiRNA‐219 is reduced in AD brain and regulates tau in vivo . MiRNA‐132 is able to protect against tauopathies . We demonstrated that in hippocampus, miRNA‐219 and miRNA‐15a were reduced post dAGEs intervention, while quercetin is able to elevate miRNA‐219 and miRNA‐15a, in addition, quercetin also elevated miRNA‐132.…”
Section: Discussionmentioning
confidence: 73%
“…However, the exact molecular mechanisms of miR‐34c and its upstream regulatory pathways in the development of AD have not yet been elucidated. Some functional miRNAs, including miR‐34 family, are differentially expressed in AD and cancer (Bhatnagar et al, ; Chamani, Sadeghizadeh, Masoumi, & Babashah, ; El Fatimy et al, ). We speculate that the tumor suppressor miR‐34c might play a role in the inverse relationship between AD and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, miR-132 functions as a key activity-dependent regulator of cognition, whose expression must be maintained within a limited range to ensure normal learning and memory formation [48]. In fact, miR-132 has been considered as a master regulator of neuronal health [49], and its supplementation is being evaluated for the treatment of diseases such as tau-associated neurodegenerative disorders [50]. Therefore, in an analogous way, miR-148b-3p might also play a role in the protection of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%